The association between watching television and obesity in children of school-age in Saudi Arabia - Sameer H Al-Ghamdi (Wolters Kluwer Medknow Publications, 2013)
Background: There is little information on the association between watching Television (TV) and obesity in the Arabian Peninsula. Aim of the Study: The aim of this study was to explore the association between the watching of television and obesity in Saudi children of school-age. Materials and Methods: A case-controlled study was conducted with students between the ages of 9 and 14 years who attended the school health clinic in King Abdulaziz Housing for National Guard (Iskan), Riyadh, Saudi Arabia, during the study period (February to April 2012). During each clinic, children were selected by simple random sampling (five obese and five non-obese). For data collection, two trained physicians interviewed the participants using a 20-item Arabic questionnaire. Well-trained nurses collected the anthropometric measurements of weight and height. Results: The study included 397 students. Higher (body mass index) BMI was associated with a higher number of televisions at home (P < 0.001), watching TV for more than three hours per day at the weekend (P = 0.047), eating more than three snacks per day (P = 0.005), watching TV at night (P = 0.026), and siblings' decisions on how much TV to watch (P = 0.025). The prevalence of childhood obesity was significantly lower among those whose mothers determined how much TV they could watch (P = 0.03). In logistic regression analysis, the increase in the child's age, the presence of more than one TV at home, having his or her own TV, and an increase in the number of hours of watching TV over the weekend were significantly associated with an increased risk of childhood obesity. Personal computers and the Internet were not significantly associated with an increased risk of childhood obesity. Conclusion: The present investigation revealed that watching TV represents an important risk factor for obesity in children of school-age.